2018
DOI: 10.1016/j.ijcard.2018.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and prediction of mortality by conventional clinical score systems according to the setting of care

Abstract: Risk scores currently adopted for decision making on starting oral anticoagulation provide good prediction of long-term survival in unselected AF patients, especially in the outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…In a paper investigating the ability of predicting all-cause death in 1051 atrial fibrillation patients, all risk scores presented modest c-indexes ranging from 0.639 for HAS-BLED to 0.706 for CHADS 2 . 28 Our results confirm and extend this evidence, supported by a detailed extensive analysis of available literature.…”
Section: Discussionsupporting
confidence: 87%
“…In a paper investigating the ability of predicting all-cause death in 1051 atrial fibrillation patients, all risk scores presented modest c-indexes ranging from 0.639 for HAS-BLED to 0.706 for CHADS 2 . 28 Our results confirm and extend this evidence, supported by a detailed extensive analysis of available literature.…”
Section: Discussionsupporting
confidence: 87%
“… 137 Notably, both diseases are promoted by inflammation and share many risk factors: hypertension, DM, sleep apnoea, obesity, and smoking. 138 Despite many authors reported an association between atherosclerosis and AF, we have limited data confirming this hypothesis in prospective cohorts of patients without clinical manifestations of AF or CAD. 139 Two large registries show a close relationship between CT assessed calcium score and later occurrence of AF, while an analysis from the Danish registry evidenced a correlation with baseline calcium score (area under the curve 0.68) especially for values ≥1000.…”
Section: Af and Comorbidities: Clinical Implications And Translational Perspectivesmentioning
confidence: 76%
“…In view of its epidemiological profile, AF affects subjects in the range of age at highest risk of adverse outcomes if infected by Sars-Cov-2 [33] and the caution in avoiding admissions to hospital may explain the important reduction in acute pharmacological and non-pharmacological treatments applied for AF in emergency setting reported during the study period, as reported in this survey. Since appropriate prescription of oral anticoagulants in patients at risk of stroke is a major determinant of outcome at long term [34][35][36][37][38][39][40], it will be necessary in the near future to establish even stricter connections between hospital and out of hospital care, for a re-assessment of patients who presented AF and these months with regard to clinical evaluation and appropriateness of treatment for ensuring continuity of care. It will also be interesting to assess to what extent untreated or undiscovered AF occurred during the lockdown will result in major consequences, such as syncope, heart failure, stroke/systemic embolism [41][42][43].…”
Section: Discussionmentioning
confidence: 99%